Energy efficiency joint optimization algorithm for mixed-ADC massive MIMO systems - Haiyan CAO; Zhongliang WANG; Hao XU; Qianhong CHEN; Fangmin XU (Dianxin kexue)
An energy efficiency optimization algorithm was proposed for the uplink of massive MIMO system with mixed precision analog-to-digital converter (ADC) at the receiver.Based on the maximum ratio combining detection algorithm (MRC), the approximate closed-form expression of system uplink energy efficiency was derived.Firstly, the proportion of high-precision ADC was determined, and then the quantization accuracy of low-resolution ADC, the user’s transmission power and the number of antennas at the base station was taken as the optimization objectives to alternately iterate to obtain the optimal energy efficiency value.Furthermore, the influence on energy efficiency and spectrum efficiency was analyzed by adjusting the proportion of high-precision ADC.The simulation results show that the proposed algorithm has high energy efficiency, and can achieve a better balance between energy efficiency and spectrum efficiency by adjusting the proportion of high-precision ADC.